Recent Development on Information System Capabilities and Sustainable Competitive Advantages: A Research Model, Review and Directions for Future Research - Mohd Jawi, Abdul Ismail Hj; Abdullah, Malvern; Ellen Chung, Chung Siew Mee (Information Management and Business Review, 2023)
In today’s competitive environment, maintaining a competitive advantage to achieve high performance is a significant challenge for businesses. To succeed, organizations must not only develop competencies in their focus areas but also be able to adapt, change, and realign those competencies in a dynamic and competitive corporate environment. As a result, information system (IS) capabilities are growing in significance as a strategic element that supports the development of competitive advantages and organizational survival. By examining the gap from the prior research, this study intends to answer questions about the link between information system (IS) related capabilities and the sustainable competitive advantages of an organization. The dimensions of information system capabilities (Personnel capability, Administrative capability, Infrastructure capability, and Information management capability) are factors that could explain a firm’s sustainable competitive advantage and the theory of dynamic capability is used as the guiding theory, as guidance, and to support the conceptual framework. This will clarify how firms may use their resources and capabilities to boost the effectiveness and utilization of information systems (IS) in daily operations, processes, and people’s performance.